2021
DOI: 10.1021/acs.orglett.1c03028
|View full text |Cite
|
Sign up to set email alerts
|

Endo Selectivity in the (4 + 3) Cycloaddition of Oxidopyridinium Ions

Abstract: The (4 + 3) cycloaddition of 2-trialkylsilyl-4-alkylbutadienes with an N-methyloxidopyridinium ion affords cycloadducts with high regioselectivity and excellent endo selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, with the larger TMS group in the same position ( 21 b ), only the endo cycloadduct 22 b was formed. This is consonant with our studies of silylated dienes in the corresponding intermolecular reaction [3a] …”
Section: Methodssupporting
confidence: 91%
“…However, with the larger TMS group in the same position ( 21 b ), only the endo cycloadduct 22 b was formed. This is consonant with our studies of silylated dienes in the corresponding intermolecular reaction [3a] …”
Section: Methodssupporting
confidence: 91%
“…The substrates for the process are known compounds, produced in our laboratories using methodology we developed for the (4 + 3) cycloaddition of oxidopyridinium ions with dienes. 4 From the very rst example of the process, we noted an interesting phenomenon. For example, entry 1 of Table 1 (see also Scheme 4) makes use of an inseparable mixture of diastereomers as the starting material.…”
mentioning
confidence: 89%
“…Furthermore, the cycloaddition process can be steered towards a high preference for the endo diastereomer when the starting diene bears a bulky trialkylsilyl groups at C2, as we have recently reported (Scheme 2). 4 Upon our initial exploration into the chemistry of the latter (4 + 3) cycloadduct products, our intentions were the replacement of the trialkylsilyl group with a halogen atom such as iodine or bromine. We were particularly inspired by a report from the Zakarian group, who showed that vinylsilanes react with Niodosuccinimide in hexauoroisopropanol to afford iodoalkenes stereospecically and in good yield (Scheme 3).…”
mentioning
confidence: 99%
“…We have been investigating the intermolecular (4+3) cycloaddition reaction of selected oxidopyridinium ions with dienes and have reported that the process is generally quite effective in terms of yield . Complete control of regioselectivity and endo / exo selectivity remain to be fully optimized, though progress has been made on both fronts. , An example is shown in Scheme . As part of that program, the chemistry of the cycloadducts has become of interest.…”
mentioning
confidence: 99%
“…The precursors used in this study are the (4+3) cycloadducts resulting from the reaction of dienes with the oxidopyridinium ion obtained from 1 upon treatment with base. Their syntheses have been reported elsewhere. , …”
mentioning
confidence: 99%